2003
DOI: 10.1023/a:1024894130989
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Previously reported effects of amrinone on skeletal muscle function suggest that the drug reduces the rate constant of myosin cross-bridge dissociation. We have used the in vitro motility assay to further elucidate the mechanism underlying this effect and to aid these studies a new, improved, filament tracking software was developed in the Matlab environment. The experiments were carried out at 30 degrees C using heavy meromyosin from fast rabbit muscle and rhodamine-phalloidin labeled actin filaments. A slowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 58 publications
5
35
2
Order By: Relevance
“…These results showed that amrinone reduces the sliding velocity ( V max ) at saturating MgATP concentrations but not at MgATP concentrations close to, or below, the K m value for the hyperbolic relationship between MgATP concentration and sliding velocity. Such a combination of effects is consistent with a reduced MgADP release rate (24) but not with competitive inhibition of substrate binding. However, effects of amrinone on the MgADP release rate have not been directly demonstrated.…”
supporting
confidence: 61%
See 2 more Smart Citations
“…These results showed that amrinone reduces the sliding velocity ( V max ) at saturating MgATP concentrations but not at MgATP concentrations close to, or below, the K m value for the hyperbolic relationship between MgATP concentration and sliding velocity. Such a combination of effects is consistent with a reduced MgADP release rate (24) but not with competitive inhibition of substrate binding. However, effects of amrinone on the MgADP release rate have not been directly demonstrated.…”
supporting
confidence: 61%
“…It has been proposed (2022) that amrinone might competitively inhibit the MgATP binding by myosin. However, more recently, results from in vitro motility assay experiments (24) challenged this idea. These results showed that amrinone reduces the sliding velocity ( V max ) at saturating MgATP concentrations but not at MgATP concentrations close to, or below, the K m value for the hyperbolic relationship between MgATP concentration and sliding velocity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The methods for protein preparations, in vitro motility assays and recording of in vitro motility assay data have been described in detail elsewhere [10, 2931]. The in vitro motility assays were performed at 25°C, pH 7.4, 1 mM MgATP, and 40 mM ionic strength.…”
Section: Methodsmentioning
confidence: 99%
“…The main mechanism of action of milrinone is, as in most of the here discussed agents, multiple. The increase in myocardial contraction is result of an altered trans-sacrolemal Ca + flux [5], the decrease in peripheral vascular resistance is a result of an increased uptake of Ca in the sarcoplasmatic reticulum and therefore a decrease in free intracellular Ca + in the smooth muscle cells of the vasculature [6] and finally, some improvement in lusitropy is considered to be a result of an enhanced dissociation of actin and myosion during diastole [7]. The vasodilatory effects of milrinone are magnified in the presence of andadrenergic agents such as phenylephrine, norepinephrine, or dopamine because of the combined activation of adenylate cyclase and inhibition of phosphodiesterase III [8,9],.…”
Section: Phosphodiesterase Inhibitorsmentioning
confidence: 99%